DOI: 10.11606/t.5.2008.tde-05082008-150405
|View full text |Cite
|
Sign up to set email alerts
|

Estudo eletromiográfico do músculo masseter em indivíduos submetidos à cirurgia de terceiros molares inferiores

Abstract: DEDICATÓRIA Utilizaram-se a terminologia e as definições estatísticas conforme o GUIA PARA EXPRESSÃO DA INCERTEZA DE MEDIÇÃO, Segunda Edição Brasileira do Guide to the Expression of Uncertainty in Measurement (BIPM, IEC, IFCC, ISSO, IUPAC, IUPAP, OIML, 1983). Edição Revisada (Agosto de 1998) -Rio de Janeiro: ABNT, INMETRO, SBM, 1998. As abreviaturas dos títulos dos periódicos de acordo com LIST OF JOURNALS INDEXED IN INDEX MEDICUS (1992) e na LILACS -LITERATURA LATINO-AMERICANA E DO CARIBE EM CIÊNCIAS DA SAÚ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Still, they described that masseter of third molar extraction side, at rest, exhibited a statistically significant increasing of the electric activity, which could be related to the presence of both swelling and inflammatory process at the surgical site, since the contralateral side did not show any differences [2]. Another study following-up the post-surgical evolution after mandibular third molar extraction through electromyography at 4 moments (preoperative, 7, 14 and 21 day postoperative) found that the comparison between the extraction and contralateral sides was almost the same [21].…”
Section: Introductionmentioning
confidence: 99%
“…Still, they described that masseter of third molar extraction side, at rest, exhibited a statistically significant increasing of the electric activity, which could be related to the presence of both swelling and inflammatory process at the surgical site, since the contralateral side did not show any differences [2]. Another study following-up the post-surgical evolution after mandibular third molar extraction through electromyography at 4 moments (preoperative, 7, 14 and 21 day postoperative) found that the comparison between the extraction and contralateral sides was almost the same [21].…”
Section: Introductionmentioning
confidence: 99%
“…Tabela 5.9 -Estudo da atividade do músculo masseter quando comparado fraturas bilaterais e unilaterais de mandíbula Gráfico 5.1 -Estudo longitudinal da média quadrática do registro da atividade elétrica ("root mean square" -RMS -V) obtida pela eletromiografia de superfície dos músculos masseter direito de cada paciente segundo a avaliação e segmentado pelo osso fraturado Gráfico 5.2 -Estudo longitudinal da média quadrática do registro da atividade elétrica ("root mean square" -RMS -V) obtida pela eletromiografia de superfície dos músculos masseter esquerdo de cada paciente segundo a avaliação e segmentado pelo osso fraturado (Figun;Garino, 1994;Hjorthet al 1997;Barros;Santos, 2008;Barros et al, 2010) Os principais ossos da face são mandíbula, maxila, nasal e zigomático. (Madeira, 2010) O tratamento para as fraturas dos ossos da face, quando possível, é o tratamento aberto, com a redução da fratura e a estabilização utilizando mini-placa e parafuso.…”
Section: Seleção Da Casuística E Critérios De Inclusãounclassified